Challenge and opportunity: The two edges of continuous-flow photochemistry - Oksdath Mansilla, Gabriela (2023)
In this Activity article, Gabriela Oksdath-Mansilla and Fabricio R. Bisogno (both professors at the Universidad Nacional de Córdoba and researchers at the National Scientific and Technical Research Council of Argentina [CONICET]) and Brenda Pijper (Horizon 2020 PhotoReAct early-stage researcher in the Chemical Technologies group at Janssen, the Pharmaceutical Companies of Johnson & Johnson) and Jesus Alcázar (head of the Chemical Technologies group at Janssen) discuss the importance of implementing continuous-flow photochemistry as a tool in drug-discovery programs as they wonder about the next challenges in the field.